Proceedings of the ITI 2009 31st International Conference on Information Technology Interfaces 2009
DOI: 10.1109/iti.2009.5196109
|View full text |Cite
|
Sign up to set email alerts
|

Exam timetabling using genetic algorithm

Abstract: In this paper we present a case study concerning the exam timetabling problem we faced, and its genetic algorithm based solution. Several variations of the algorithm as well as the influence of algorithm parameters are analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The software program developed to provide more effective education and training uses the efficiency of education and teaching and the weight of the course as criteria. Although there are many studies in the literature about solving the problem of exam scheduling by genetic algorithm [15][16][17], there are not many studies for central examinations. In addition, there are different studies [18][19][20][21][22][23][24] that seek solutions to the problem of exam scheduling with different techniques such as fuzzy logic and data mining.…”
Section: Related Studiesmentioning
confidence: 99%
“…The software program developed to provide more effective education and training uses the efficiency of education and teaching and the weight of the course as criteria. Although there are many studies in the literature about solving the problem of exam scheduling by genetic algorithm [15][16][17], there are not many studies for central examinations. In addition, there are different studies [18][19][20][21][22][23][24] that seek solutions to the problem of exam scheduling with different techniques such as fuzzy logic and data mining.…”
Section: Related Studiesmentioning
confidence: 99%
“…Objective function will be used to figure out whether the proposed exam timetable is feasible or not compared to the previous exam timetable. A recent study by Cupic et al (2009) found that the objective function of timetabling refers to the weighted penalty, which is assigned to soft constraints that are not satisfying. Therefore, clustering heuristic will be applied in this study to split exams into groups and conflict between exams which is represented by conflict matrix.…”
Section: The Studymentioning
confidence: 99%
“…The aim of an exam timetable is to guarantee that all exams are scheduled and students can sit all the exams that they are required to do. The objective function in timetabling refers to weighted penalty, where it is assigned to soft constraints that are not satisfied [5].…”
Section: Examination Timetablingmentioning
confidence: 99%